PERTANGGUNGJAWABAN PIDANA TERHADAP KORPORASI DALAM PENCEMARAN LINGKUNGAN HIDUP (SUATU ANALISIS NORMATIF) - Ruslan Abdul Gani (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This research aims to investigate the Criminal Liability of Corporations in environmental pollution (an analysis of the juridical Normative) and Criminal Liability Could studies stresing Against Corporations In pollution of the environment, how does the Criminal Liability of corporations, Properties and Constraints in law enforcement (Criminal) against the Corporation and effort Penanggulangannya. with the approach of the legislation's future is expected to open up the opportunity for researchers to learn is there consistency and alignment of one act with its implementation in the field. The results showed that the criminal liability of Corporations in pollution of the environment in principle there are three groups that can be accounted for in a corporation doing criminal acts as a private person, yait is doing, as the Governing Board of legal entities and legal entities themselves. Seen from the nature of Corporate criminal liability in principle there are three types namely: the first Governing Board of the Corporation as the creator and administrator is responsible. Both Corporations as makers and responsible sysop.The third Corporation as maker and also as responsible. Constraints in law enforcement (Criminal) against the Corporation in the municipality incur three factors i.e., Legal Factors, Factor, factor Means law enforcement While efforts are being made in overcoming the obstacles that occur are legal sanctions imposed upon the perpetrator heavier again so that it can carry a deterrent effect.Keywords: Criminal Liability of Corporations In the environment.